Veränderungen von Wohlbefinden und privater Unterstützung für Ältere: ein Blick auf die Auswirkungen der COVID-19-Pandemie im Frühsommer 2020 - Brandt, Martina (Z Gerontol Geriatr, 2021)
BACKGROUND: The pilot study “Health and Support in Times of Corona” (TU Dortmund University) collected data on support and well-being of individuals aged 40 plus years in the light of the first wave of the COVID-19 pandemic from May to July 2020. OBJECTIVE: The aim was to study the social and mental effects of the pandemic. We focused on individuals living in private households aged 40 years and older. Participants were asked about pandemic-related changes in receiving and providing support (e.g. personal care, help with household chores), problems arising in taking care of older persons and changes in well-being. MATERIAL AND METHODS: We conducted descriptive and multivariate analyses to show how support changed, problems with support came up and well-being changed in the light of the pandemic and how all this was related. RESULTS: Due to the pandemic older respondents in particular were no longer able to provide the necessary support for others. Especially women reported problems in taking care of older individuals. We found a decrease in well-being for all respondents but most significantly for women and individuals aged 80 years and older. Moreover, problems in the provision of care due to the pandemic and lower well-being were clearly linked. CONCLUSION: Our study showed significant changes in support patterns and well-being due to the COVID-19 pandemic. A substantial part of the respondents reported more loneliness and lower life satisfaction compared to before the pandemic, especially women supporting others. In these pandemic times, informal caregiving is severely hampered. Future pandemic-related measures should be carefully planned bearing such issues in mind.